Weather studies - Smith, M. P. (Lionel Percy), 1914- (Commonwealth and international library. Selected readings in analytical chemistry., 1966)
Weather Studies presents thorough discussions on various aspects of weather and weather studies. This text first presents the methods of measuring the weather, including measuring the temperature, humidity, rainfall, snowfall, visibility, wind force and direction, and pressure. Then, this book explains how to put these measurements in graphs to better present the data. This topic is followed by discussions on "weather in pairs,₄ or the relationships of weather measurements, such as of temperature and pressure, wind, and humidity, as well as of visibility and wind direction and humidity. This b.